The Essential Nietzsche : Beyond Good and Evil and The Genealogy of Morals. - Nietzsche, Friedrich (Book Sales, 2017)
A bind up of Nietzsche's two most famous works; Beyond Good and Evil (1886) and Genealogy of Morals.